A new path-independent variable to model ductile damage. Issue 4 (4th March 2023) - Krishnaswamy, Hariharan; Balaji, Vikram; Bharti, Sahil
ABSTRACT: The effective plastic strain is a commonly used damage variable within continuum damage framework. The value of effective plastic strain at fracture, however, depends on strain rate, temperature and strain path. An alternate state variable is proposed in this work that can provide a unique path-independent 2 fracture locus. The average dislocation density is a microstructure-based state variable and has been established in the past to describe the constitutive behaviour of plastic deformation. It is demonstrated that when the average dislocation density is used to model fracture initiation, the fracture locus is unique over a range of strain rates, unlike the conventionally used fracture strain.